Assessing response to interferon-β in a multicenter dataset of patients with MS. (12th July 2016) - Sormani, Maria Pia; Gasperini, Claudio; Romeo, Marzia; Rio, Jordi; Calabrese, Massimiliano; Cocco, Eleonora; Enzingher, Christian; Fazekas, Franz; Filippi, Massimo; Gallo, Antonio; Kappos, Ludwig; Marrosu, Maria Giovanna; et al.
Abstract : Objective: To provide new insights into the role of markers of response to interferon-β therapy in multiple sclerosis (MS) in a multicenter setting, focusing on the relevance of MRI lesions in combination with clinical variables. Methods: A large multicenter clinical dataset was collected within the Magnetic Resonance Imaging in MS (MAGNIMS) network. This included a large cohort of patients with relapsing-remitting MS on interferon-β treatment, MRI and clinical assessments during the first year of treatment, and clinical follow-up of at least 2 additional years. Heterogeneity among centers was assessed before pooling the data. The association of 1-year MRI or clinical relapses with the risk of treatment failure (defined as Expanded Disability Status Scale [EDSS] worsening or treatment switch for inefficacy) and of EDSS worsening alone was evaluated using multivariate Cox models. Results: A pooled dataset of 1, 280 patients with relapsing-remitting MS from 9 MAGNIMS centers was analyzed. The risk of failure had a relevant increase with 1 relapse (hazard ratio [HR] 1.84, 95% confidence interval [CI] 1.39–2.44, p < 0.001) and ≥3 new T2 lesions (HR 1.55, 95% CI 0.92–2.60, p = 0.09). In patients without relapses and less than 3 new T2 lesions, the 3-year risk of failure and EDSS worsening were 17% and 15%; in patients with 1 relapse or ≥3 new T2 lesions, the risks were 27% and 22%; in patients with both conditions or more than 1 relapse, the risks were 48% ( p < 0.001) and 29% ( p < 0.001). Conclusions: Substantial MRI activity, particularly if in combination with clinical relapses, during the first year of treatment with interferon-β indicates significant risk of treatment failure and EDSS worsening in the short term.